Chemical characterization of pro-inflammatory amyloid-beta peptides in human atherosclerotic lesions and platelets - Kokjohn, Tyler A. (2011)
Amyloid-β (Aβ) peptides are intimately involved in the inflammatory pathology of atherosclerotic vascular disease (AVD) and Alzheimer's disease (AD). Although substantial amounts of these peptides are produced in the periphery, their role and significance to vascular disease outside the brain requires further investigation. Amyloid-β peptides present in the walls of human aorta atherosclerotic lesions as well as activated and non-activated human platelets were isolated using sequential size-exclusion columns and HPLC reverse-phase methods. The Aβ peptide isolates were quantified by ELISA and structurally analyzed using MALDI-TOF mass spectrometry procedures. Our experiments revealed that both aorta and platelets contained Aβ peptides, predominately Aβ40. The source of the Aβ pool in aortic atherosclerosis lesions is probably the activated platelets and/or vascular wall cells expressing APP/PN2. Significant levels of Aβ42 are present in the plasma, suggesting that this reservoir makes a minor contribution to atherosclerotic plaques. Our data reveal that although aortic atherosclerosis and AD cerebrovascular amyloidosis exhibit clearly divergent end-stage manifestations, both vascular diseases share some key pathophysiological promoting elements and pathways. Whether they happen to be deposited in vessels of the central nervous system or atherosclerotic plaques in the periphery, Aβ peptides may promote and perhaps synergize chronic inflammatory processes which culminate in the degeneration, malfunction and ultimate destruction of arterial walls.